Bibliometric Analysis of Decision-Making Models in The Context of Bounded Rationality - Ananda Lydia Putri Salwa; Kaisar Khoirul Alwan; Muhammad Rizqullah; Risna Lulu'ul Maknun; Sabrina Perlita; Margareth Henrika; Muhammad Ramadhani Kesuma (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study maps the intellectual landscape of decision-making models within the bounded rationality framework, specifically as it applies to financial management research. A systematic bibliometric analysis was conducted on publications retrieved from Scopus and Web of Science, covering the period from the 2000 to 2026 and analyzed using VOSviewer software.Publication trends exhibit a fluctuating yet upward trajectory concentrated in the most recent period, while inter-author and inter-country collaboration networks remain underdeveloped. Keyword co-occurrence analysis identifies bounded rationality as the conceptual core of the field, with visible thematic evolution from formal decision theory toward behavioral finance and artificial intelligence integration.Financial practitioners and policymakers should incorporate behavioral and cognitive constraints into decision-support frameworks, particularly in investment and risk management contexts.This paper contributes a systematic cartography of bounded rationality scholarship in financial management, identifying understudied themes and open directions for future research.